MOVIES VS. DIGITAL MEDIA: EFFECTIVENESS IN ENGLISH VOCABULARY AND GRAMMAR ACQUISITION AMONG EFL LEARNERS IN CENTRAL ASIA (Ustozlar uchun, 2026)
Digital media platforms have fundamentally transformed the landscape of informal language learning, presenting both unprecedented opportunities and complex pedagogical challenges for English as a Foreign Language (EFL) instruction. While prior investigations have examined the discrete effects of specific media types on language acquisition, relatively few studies have undertaken a rigorous comparative analysis of the differential effectiveness of full-length motion pictures versus short-form digital media — specifically YouTube videos and television series — in facilitating vocabulary enrichment and grammatical competence among undergraduate EFL learners. The present study addresses this research gap by conducting a systematic comparative investigation among fifty undergraduate English-major students enrolled at a higher education institution in Kazakhstan. Employing a mixed-methods research design that integrates quantitative survey instruments with qualitative semi-structured interview protocols, the study explores the extent to which each media category contributes to measurable gains in lexical breadth and grammatical accuracy, and examines the mediating roles of learner motivation, media preference, and frequency of engagement. The findings of this investigation are anticipated to yield substantive theoretical insights and practical pedagogical recommendations for EFL educators seeking to leverage digital media resources as effective supplementary instructional tools in Central Asian educational contexts.